2016
DOI: 10.1289/ehp234
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Deposition, Translocation, and Microglial Activation of Inhaled Silver Nanoparticles in the Rodent Nose and Brain

Abstract: Background:Silver nanoparticles (AgNP) are present in personal, commercial, and industrial products, which are often aerosolized. Current understanding of the deposition, translocation, and health-related impacts of AgNP inhalation is limited.Objectives:We determined a) the deposition and retention of inhaled Ag in the nasal cavity from nose-only exposure; b) the timing for Ag translocation to and retention/clearance in the olfactory bulb (OB); and c) whether the presence of Ag in the OB affects microglial act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 30 publications
(64 reference statements)
2
55
0
2
Order By: Relevance
“…In relation to the CNS, it has been shown that AgNPs, following inhalation and ingestions, cross the BBB and accumulate in the brain [90][91][92]. Patchin et al found rapid translocation of 20 nm AgNPs into the olfactory bulb, with slower and less effective transport of 110 nm silver particles after a 6-h exposure [93]. A study reported very little AgNP absorption (measured as total silver) into the blood after intranasal administration and significantly higher blood concentrations after AgNO3 delivery, and demonstrated that silver found in the blood was due to silver ion release from AgNPs [94].…”
Section: Silver Nanoparticlesmentioning
confidence: 99%
“…In relation to the CNS, it has been shown that AgNPs, following inhalation and ingestions, cross the BBB and accumulate in the brain [90][91][92]. Patchin et al found rapid translocation of 20 nm AgNPs into the olfactory bulb, with slower and less effective transport of 110 nm silver particles after a 6-h exposure [93]. A study reported very little AgNP absorption (measured as total silver) into the blood after intranasal administration and significantly higher blood concentrations after AgNO3 delivery, and demonstrated that silver found in the blood was due to silver ion release from AgNPs [94].…”
Section: Silver Nanoparticlesmentioning
confidence: 99%
“…A variety of materials have been utilized for nanoparticle delivery to the brain, including dendrimers, polymers, micelles, hydrogels, liposomes and solid lipids, gold, silica, silver‐based inorganics, iron or iron oxides, quantum dots, and carbon‐based particles . For each of these nanoparticle systems, important physicochemical characteristics that affect drug delivery and efficacy include size, surface charge, composition, molecular weight (MW), material structure, elasticity, shape, and material porosity (Table ).…”
Section: Nanoparticle Physicochemical Properties For Overcoming Physimentioning
confidence: 99%
“…При этом респираторная система рассматривается в качестве одной из основных портальных систем для поступления наноча-стиц в организм. Однако, помимо очевидного воздействия наноаэрозолей на респираторную и сердечнососудистую системы, частицы могут захватываться ольфакторным эпителием носовой полости и проникать в центральную нервную систему (ЦНС) в обход гематоэнцефалического барьера, где способны ускорять развитие нейродегенера-тивных заболеваний (Genter et al, 2012;Heusinkveld et al, 2016;Parmalee, Aschner, 2016;Patchin et al, 2016). Нейро паталогии, возникающие в результате воздействия на организм наноаэрозолей, трудно исследовать вследствие отсроченного характера их возникновения.…”
unclassified
“…Нейрональный захват (ольфакторные нейроны, нейро-ны тройничного нерва) и их последующий аксональный транссинаптический транспорт в более глубокие струк-туры мозга -наиболее вероятный путь проникновения твердых частиц из носовой полости в мозг (Elder et al, 2006;Genter et al, 2012;Patchin et al, 2016). Участие клеточного транспорта в перемещении твердых частиц из носовой полости в мозг впервые показано на примере нейротропных вирусов.…”
unclassified